Direct measurement of nanomechanical actuation across phase transition in VO2 crystals. (December 2017) - Singh, Davinder; B., Viswanath
Abstract: We employ in situ nanoindentation method to measure spontaneous strain during thermally induced structural phase transition in VO2 crystals. Large tip displacement of ~ 520 nm is observed normal to (011) facet of VO2 crystals during phase transition. The captured actuation signals in the form of tip displacement from VO2 indicate 0.53% of spontaneous strain normal to (011) facet during phase transition. Spontaneous strain across phase transition is found to be reversible over thermal cycles with different heating rates. The investigated aspects demonstrate the application of nanoindentation in quantifying actuation of VO2 micro crystals towards highly efficient thermal actuators. Graphical abstract: